2009
DOI: 10.1530/rep-08-0117
|View full text |Cite
|
Sign up to set email alerts
|

Vascular supply as a discriminating factor for pig preantral follicle selection

Abstract: This research analyses how somatic and vascular compartments change during preantral follicle growth. To address this aim, theca-granulosa (somatic) proliferation indexes (PIs), proportion of proliferating endothelial cells (PE), vascular area (VA) and vascular endothelial growth factor A (VEGFA) expression were simultaneously recorded on single healthy preantral follicles, classified into six different stages on the basis of the diameter and the granulosa layers. An autonomous blood vessel network starts to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 62 publications
1
34
0
1
Order By: Relevance
“…The higher S1P and CER concentrations found in our study in the theca cell layer as compared with the granulosa cells, for both types of follicles, may be explained by the rich vasculature that exists in internal and external theca cells, and the resulting increase in endothelial cells (40%) (Martelli et al, 2009). It was shown that aortic bovine endothelial cells are rich in sphingomyelinases, which synthesise CER (Mulders et al, 2007).…”
Section: Discussionmentioning
confidence: 42%
“…The higher S1P and CER concentrations found in our study in the theca cell layer as compared with the granulosa cells, for both types of follicles, may be explained by the rich vasculature that exists in internal and external theca cells, and the resulting increase in endothelial cells (40%) (Martelli et al, 2009). It was shown that aortic bovine endothelial cells are rich in sphingomyelinases, which synthesise CER (Mulders et al, 2007).…”
Section: Discussionmentioning
confidence: 42%
“…Blood vessels allow growing follicles to acquire an increasing amount of nutrients, precursors, and hormones, as to release steroids and other regulating ovarian hormonal molecules to the systemic circulation [8], [13]. Several factors drive follicle angiogenesis indirectly controlling ovarian follicle development [6], [7], [11], [14][16]. VEGF is recognized to be a key molecule [13], [16], [17].…”
Section: Introductionmentioning
confidence: 99%
“…gonadotropins and growth factors, and oxygen and metabolites via the blood stream. Early follicle stages depend upon the vascular system of the ovarian stroma for their supply, whereas antral follicles have an autonomous capillary network provided by the theca interna and externa [17], [18]. The establishment of the thecal vascular network is induced and regulated by granulosa cell-secreted factors such as vascular endothelial growth factor (VEGF), basic fibroblast growth factor (FGF2), epidermal growth factor, IGF-1 and transforming growth factor β (TGFβ) (reviewed in [18]).…”
Section: Introductionmentioning
confidence: 99%